2017
DOI: 10.1249/mss.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Pediatric Obesity

Abstract: Purpose We aimed to determine if moderate-to-vigorous physical activity (MVPA) and sedentary behavior (SB) were independently associated with body mass index (BMI) and waist circumference (WC) in children and adolescents. Methods Data from the International Children’s Accelerometry Database (ICAD) were used to address our objectives (N=11,115; 6-18y; 51% female). We calculated age and gender specific body mass index (BMI) and waist circumference (WC) Z-scores and used accelerometry to estimate MVPA and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
8
18
0
9
Order By: Relevance
“…Our results showed that sedentary behavior was positively associated with central adiposity. In agreement with our results, a previous cross‐sectional study found that each increment in 1 hour of sedentary behaviors was associated with 0.05 cm higher waist circumference in healthy children and adolescents from Europe, the United States of American, Brazil, and Australia …”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that sedentary behavior was positively associated with central adiposity. In agreement with our results, a previous cross‐sectional study found that each increment in 1 hour of sedentary behaviors was associated with 0.05 cm higher waist circumference in healthy children and adolescents from Europe, the United States of American, Brazil, and Australia …”
Section: Discussionsupporting
confidence: 93%
“…In general, our findings support the results of other recent empirical studies by Katzmarzyk and colleagues (16), Mitchell and colleagues (23), and Riddoch and colleagues (28) as well as a systematic review by Kelley and colleagues (17). When coupled with these reports, our study suggests that the correct metabolic target for reducing the incidence of childhood obesity is at least moderate-intensity PA. We speculate that MVPA involves different physiological mechanisms than LPA (9,25).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, Mitchell et al also concluded that TV was positively associated with adiposity, independently of SED and MVPA (23). It is possible that self-reported TV viewing better represents true sedentary behavior than low accelerometer activity counts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations